A10 CORE-1 DERIVED O-GLYCOSYLATION OF THE MUCIN MUC2 PLAYS A KEY ROLE IN HOST DEFENSE AGAINST ENTERIC CITROBACTER RODENTIUM INFECTION - Celiberto, L S (J Can Assoc Gastroenterol, 2018)
BACKGROUND: Enteric bacterial pathogens are a major cause of diarrheal disease in developed as well as developing countries. To infect their hosts, most pathogens need to directly infect the intestinal epithelium, however to do so, they must cross the overlying intestinal mucus layer. Intestinal mucus is predominantly comprised of the mucin Muc2, a highly O-glycosylated protein with core 1 and core 3 derived O-glycans as its primary constituents. We previously showed that mice lacking Muc2 are highly susceptible to infection by Citrobacter rodentium, a mouse specific relative of the bacterial pathogen enterohemorrhagic E. coli, with Muc2 deficient mice carrying high pathogen burdens as well as suffering severe intestinal inflammation and epithelial damage. At present, it is unclear whether the protection provided by Muc2 reflects the actions of the Muc2 protein, its glycosylation, or both. AIMS: The aim of this study was to explore the role of Muc2 glycosylation in providing host defense in mice challenged with C. rodentium, by comparing the susceptibility of mice lacking Muc2, core 1 glycosylation or core 3 glycosylation. METHODS: Six to ten week old WT, C1galt1(f/f) , C1galt1(-/-), Core 3(-/-)and Muc2(-/-) mice were infected with C. rodentium by oral gavage. Mice were monitored daily for morbidity throughout the experiment and were euthanized at day 6 of infection. Several tissues of interest were collected to verify bacterial colonization in the gut and at systemic sites. For histology, colon and cecum tissues were stained with hematoxylin-eosin, mounted on microscope slides and scored based on previously adapted scoring systems. RESULTS: Mice lacking core 3 glycosylation were roughly similar to WT mice in their modest susceptibility to C. rodentium infection. In contrast, mice expressing Muc2, but lacking core 1 glycosylation (C1galt1(-/-) mice) were similar to Muc2(-/-) mice in terms of showing increased susceptibility to C. rodentium characterized by dramatically increased intestinal and systemic pathogen burdens, greater macroscopic damage to the epithelium, thickening of the colon and shrinkage of the cecum. The results were compared to mice with loxP sites flanking C1galt1 (C1galt1(f/f) ). Histological samples of C1galt1(-/-) and Muc2(-/-) mice showed significantly higher pathology score in comparison with C1galt1(f/f) demonstrated by severe edema, loss of epithelial integrity, crypt hyperplasia, and goblet cell depletion. CONCLUSIONS: This study demonstrates that the protective role played by Muc2 in this model reflects its glycosylation, rather than the protein itself. These findings underscore the need for further exploration of the mechanisms by which the mucus layer protects the intestinal tract from bacterial pathogens and other noxious stimuli. FUNDING AGENCIES: CCC, CIHRNSERC